Finite-time pinning stabilization of Markovian jump Boolean networks. Issue 11 (July 2020) - Zhang, Qiliang; Feng, Jun-e; Yan, Yongyi
Abstract: Finite-time stabilization problem of Markovian jump Boolean networks is investigated via pinning control in this paper. Firstly, on the basis of converting Markovian jump Boolean networks into Markov chains, a necessary and sufficient condition for the finite-time stabilization of Markovian jump Boolean networks is put forward. Secondly, an algorithm for calculating minimum number of pinning nodes is devised by altering the transition probability matrix of Markov chains. Furthermore, after the pinning nodes and the stable transition matrix are determined, a method for designing all the required pinning state feedback controllers is proposed. Finally, a biological example is presented to illustrate the feasibility of theoretical results.